The Impact of Global Economic Policy Uncertainty and Volatility on Stock Markets: Evidence from Islamic Countries - Adam, Norashikin; Sidek, Noor Zahirah Mohd; Sharif, Arshian (Asian Economic and Financial Review, 2022)
This study investigates the impact of uncertainty and volatility on ten Islamic stock returns using monthly data for from 2011:M5 to 2021:M5. We rely on the continuous wavelet transform and wavelet coherence ratios, which allows decomposition of time series across time scales to investigate the causal relationship between stock market returns, economic policy uncertainty and volatility. Our results provide some interesting insights. First, economic policy uncertainty, in general, has a negative effect on the majority of Islamic stock returns, except for the Dow Jones Islamic Market (DJIM). Second, volatility has a significant positive impact on most of the Islamic stock returns in various countries. Third, both economic policy uncertainty and volatility have a greater impact on the Islamic stock returns post-COVID-19 outbreak. These results should assist investors to re-evaluate their portfolios to fully maximize the potentials of these Islamic stock markets. Policymakers could use these results to design policies to reduce economic policy uncertainty as well as to cushion the impact of externally generated uncertainties.